Microporous Hybrid Films from Amphiphilic Copolymers: Surface Coated with Zns Nanoparticles Using the Breath Figure (Bf) Methodology - Sanchez-Poblete, J (Springer, 2020)
Abstract: High-performance catalysts and photovoltaics form key components for various technological applications. Because catalytic and photovoltaic reactions occur at the interfaces between reactants and surfaces, the chemical, physical, and structural properties of interfaces have been the focus of many studies. One route towards the improvement and optimization of such interfaces is the preparation of microporous materials from amphiphilic copolymers, which can also be surface coated with inorganic nanoparticles to obtain different properties. In this work, we have prepared microporous hybrid films with fluorescent properties from amphiphilic block copolymers surface coated with ZnS (NPs) based on the breath figure (BF) mechanism, keeping constant the concentration of ZnS NPs, solvent, humidity and substrates. The morphological and optical properties were investigated by microscopic and optical characterization techniques. As a result, the fabrication method facilitates the preparation of fluorescent porous films with varying morphological properties (shapes and diameter pore). The hybrid porous films containing polystyrene-b-polyacrylic acid, polystyrene-b-polyitaconic acid and polystyrene-b-polydialylmalonic acid were obtained with an average pore size of 0.57 ± 0.04 μm, 0.78 ± 0.03 μm and 1.50 ± 0.04 μm, respectively. An increase in the water contact angle (WCA) was observed in the block copolymer porous films after functional process with ZnS (NPs). Graphic abstract: [Figure not available: see fulltext.]. © 2020, Institute of Chemistry, Slovak Academy of Sciences.